PRAKTIK SOSIAL PADA PEREMPUAN ORGANISATORIS DI LINGKUNGAN KAMPUS: STUDI PADA MAHASISWA SOSIOLOGI UNIVERSITAS NEGERI SURABAYA DENGAN MAHASISWA UNIVERSITAS TRUNOJOYO MADURA - Laia Laia; Ahmad Ridwan (LENTERA: JOURNAL OF GENDER AND CHILDREN STUDIES, 2025)
Women's participation in various student organizations is a social phenomenon that embodies gender equality in the campus environment. Traditionally, organizational activities have been dominated by men, but this situation has gradually changed with the growing representation of women in various leadership roles. Higher education institutions, as educational bodies, play a strategic role in shaping students' social practices, particularly female students who are active in organizations. The cultural differences between the student organizations of Sociology at Unesa and UTM present an interesting factor to explore how the social practices of female organizers are formed and interpreted. Using a qualitative approach, the research was conducted through in-depth interviews with female students who are members of student organizations from the Sociology program to obtain accurate data and information. This study aims to explore gender equality among women in the campus organizational scope of two different institutions. It is expected that this research will provide practical and theoretical benefits to readers and the public. Keywords: Women, Organizational, Organization, Student Organizations.